THE NEED FOR THE INCLUSION OF DISABLED STUDENTS IN REGULAR PUBLIC SCHOOLS: A BIBLIOGRAPHIC REVIEW - Rodrigues Maia, Felipe (Revista Gênero e Interdisciplinaridade, 2023)
The main focus of the work is the search for information about the need to include students with disabilities in the school environment, as this is one of the main difficulties encountered today by parents and students themselves when entering the school environment, often due to bad reasons. adaptation or projection of the school that does not have access ramps for wheelchair users, does not have handrails with Braille identification for the visually impaired, among others. The autistic or gifted student also feels excluded and it is in this bias that we also sought to identify and direct some schools by the search for trained professionals who understand such inclusion realities when, in most cases, there is unpreparedness and even a refusal to deal with them. with this student.